Properties of the isolated solutions bounded on the entire axis for a system of nonlinear ordinary differential equations - Abildayeva, A. D.; Dzhumabaev, D. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the conditions of continuous dependence on the right-hand side for the “isolated” solutions of a system ofnonlinear ordinary differential equations bounded on the entire axis.